Pattern of computer vision syndrome in post COVID period in patients attending a tertiary hospital of central Nepal - Dahal, Polina; Subedi, Anil; Bhattarai, Ujjwol; Chaulagain, Rajib (Journal of Chitwan Medical College, 2025)
Introduction: The increasing use of digital devices has led to a rise in Computer Vision Syndrome (CVS), characterized by ocular and musculoskeletal symptoms. This study aims to determine the pattern of CVS in the post-COVID period among patients attending the ophthalmology outpatient department of Chitwan Medical College, Nepal. Method: A hospital-based cross-sectional study was conducted in the ophthalmology outpatient department of Chitwan Medical College from 01 Nov 2023 to 30 Apr 2024. After ethical approval (CMC-IRC/080/081-055) and informed consent, consecutive patients with asthenopic complaints using Visual Terminal Displays were enrolled through convenience sampling method. Data collected using a structured proforma and analysed descriptively using SPSS 26. Result: Among 331 patients with CVS, most affected age group was 16-25 years 157(47.4%), males 179(54.1%), students 218(65.8%), 151(45.6%) reported foreign body sensation, 148(44.7%) followed by burning sensation, 169(51.1%) had refractive error most commonly simple myopia 96(29.0%), and 174(52.6%) had mild dry eyes, poor sleep pattern in 74(22.4%), at least one Musculoskeletal pain in 217(65.5%). Dual device users were175(52.9%), and 133(40.2%) had screen time 4-6 h/day, and preventive measures was used by 150(45.3%), 18(5.4%) followed 20-20-20 rule and only 7(2.1%) maintained the screen distance. Conclusion: In this study CVS in the post-COVID period was most common among students and bankers with history of prolonged screen time, using multiple devices, and lack of preventive measures contribute to its severity. Awareness campaigns emphasizing preventive strategies, including ergonomic practices and screen time regulation, are essential to mitigate its impact.